ANÁLISE DA RELEVÂNCIA DA ESPIRITUALIDADE ENTRE ESTUDANTES DO CURSO DE ENFERMAGEM DA UNIEVANGÉLICA COMO FATOR DE PRESERVAÇÃO DA SAÚDE MENTAL AO LONGO DA GRADUAÇÃO (CIPEEX, 2026)
Introduction: Spirituality is an important resource for promoting mental health, especially among healthcare students, who face high levels of stress, anxiety, and academic overload. Objective: To interpret the academic reality of students enrolled in the Nursing program at the Evangelical University of Goiás - Anápolis Campus regarding their mental health and determine the influence of spirituality on this perspective. Method: This is a descriptive, cross-sectional, qualitative study conducted with 100 nursing students from UniEvangélica. Scales were applied to assess spirituality, mental health, and socioeconomic profile. Data were analyzed in SPSS 16.0 using descriptive statistics and correlation tests, considering p
Keywords: espiritualidade; estudantes de enfermagem; saúde mental